Extracting key factors for sustainable development of enterprises : Case study of SMEs in Taiwan - Matinaro, Ville; Liu, Yang; Lee, Tzong-Ru (Jiun-Shen); Poesche, Jurgen (Elsevier, 2019)
In general, enterprises should pay close attention to sustaining sufficient competitiveness in turbulent global business environments that focus on sustainable operations, especially environmental issues. It is obligated for enterprises to protect the environment, utilize sustainable resources and establish eco-industries. Many large enterprises have joined the World Business Council for Sustainable Development (WBCSD). However, the small and medium-sized enterprises (SMEs) pay various degrees of attention to environmental issues and sustainable operations. This paper investigates the sustainable development and innovation of 233 SMEs in Taiwan to find out how to develop a business model that helps them operate in a more sustainable and environmentally friendly way. According to our results, a sustainable business model is a key factor for competitive advantages with straightforward connections to business success. Results also indicate that a sustainable business model is performed with the agreement of colleagues in an organization and it requires comprehensive strategic efforts. This study has limited findings to show the insights of Taiwanese SMEs and should not be generalized in other contexts.
Keywords: Sustainable business models; Key success factors (KFSs); Grey relational analysis (GRA); Small and medium size enterprises (SMEs); fi=Tuotantotalous|en=Industrial Management|